Experience-Based Knowledge in Islamic Perspective - Sari, Yuli Indah; Mislan Cokrohadisumarto, Widiyanto bin; Fachrunnisa, Olivia; Ismail, Abdul Ghafar (International Journal of Islamic Business and Economics (IJIBEC), 2021)
The development of technology has created problems regarding challenges and opportunities in utilizing knowledge obtained by humans from various experiences. Experience-based knowledge has been seen as a special advantage for individuals and Islam has a unique way to explain this aspect. This paper aimed to develop an experience-based knowledge model from an Islamic perspective. This study used a qualitative approach based on literature reviews sourced from Al-Qur’an, Al-Hadith, and relevant previous kinds of literature. This study is expected to provide contributions to the development of theories related to experience-based knowledge from an Islamic perspective. The results show that knowledge could be learned and obtained by humans from various experience sources, such as personal experiences, other people's experiences, experts’ experiences, and experiences said in Al-Qur’an and Al-Hadith. This experience-based knowledge helped individuals improve their abilities and were disseminated to the other individuals for Allah’s blessings and achieving the embraced organizational goals and success.